Comparison of a high sensitivity and standard C reactive protein measurement in patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis. Issue 7 (24th May 2010) - Poddubnyy, DA; Rudwaleit, M; Listing, J; Braun, J; Sieper, J
Abstract : Objective: This study was aimed at comparing high sensitivity C reactive protein (hsCRP) measurement with routine C reactive protein (CRP) evaluation as disease activity parameters in patients with ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nrSpA). Methods: A total of 269 patients (153 with AS and 116 with nrSpA) were included. Level of hsCRP was measured using particle-enhanced immunoturbidimetric method with the lowest detected level of 0.1 mg/litre. The hsCRP values were compared to results of routine turbidimetric CRP test with the lowest detected level of 6 mg/litre. Results: In the whole group of patients with AS, hsCRP showed a better than routine CRP correlation with clinical parameters. In the whole group of patients with nrSpA, hsCRP correlated with the level of enthesitis-related tenderness only. In the AS subgroup with a negative routine CRP (<6 mg/litre) there was a clear trend for an increased level of pain, stiffness and functional impairment in patients with higher hsCRP concentration. Such a trend was less pronounced in patients with nrSpA. Conclusions: hsCRP correlates better than routine CRP with clinical disease activity parameters in patients with axial SpA, especially in AS. Therefore, hsCRP could be superior to standard CRP in assessing disease activity in axial SpA.